Mechanism and Kinematics for Flapping Wing Micro Air Vehicles Maneuvering Based on Bilateral Wings - Rui Zhang; Haiyang Zhang; Lichao Xu; Peng Xie; Jing Wu; Chao Wang (International Journal of Aerospace Engineering)
With the development and application of a bionic flapping micro aircraft vehicle (FMAV), further requirements for its high maneuvering flight characteristics have been put forward. A controlling tail cannot meet the requirements of the maneuvering flight of insect-sized FMAVs, and it has become necessary to find new mechanisms for high maneuvering flight. In this study, two flapping mechanisms with movable hinges based on a double crank rocker mechanism (DCRM) and a single crank slider mechanism (SCSM) are proposed. The instantaneous flapping angles, their extremum and means, and the flapping amplitudes of the two mechanisms are studied for various hinge offsets. A comparison between these two mechanisms indicates that the mechanism based on SCSM is more appropriate in providing adjustable flapping amplitudes for lateral wings. Finally, a dragonfly-like prototype assembled using a carbon fiber plate with adjustable wings is designed and manufactured based on the SCSM. Flight tests are conducted to show that the rack and pinion mechanism can accomplish the movement of hinges neatly, and the proposed flapping mechanism makes left turns and right turns effectively while continuing to fly forward. The prototype is good in terms of crashworthiness and the replacement of components, and it offers an easy and reliable technique for the maneuvering flight of FMAVs.